Sclerotherapy of lower limb veins: Indications, contraindications and treatment strategies to prevent complications – A consensus document of the International Union of Phlebology-2023. (May 2023) - Wong, Mandy; Parsi, Kurosh; Myers, Kenneth; De Maeseneer, Marianne; Caprini, Joseph; Cavezzi, Attilio; Connor, David E; Davies, Alun H; Gianesini, Sergio; Gillet, Jean-Luc; Grondin, Louis; Guex, Jean-Jérôme; et al.
Background: Sclerotherapy is a non-invasive procedure commonly used to treat superficial venous disease, vascular malformations and other ectatic vascular lesions. While extremely rare, sclerotherapy may be complicated by serious adverse events. Objectives: To categorise contraindications to sclerotherapy based on the available scientific evidence. Methods: An international, multi-disciplinary panel of phlebologists reviewed the available scientific evidence and developed consensus where evidence was lacking or limited. Results: Absolute Contraindications to sclerotherapy where the risk of harm would outweigh any benefits include known hypersensitivity to sclerosing agents; acute venous thromboembolism (VTE); severe neurological or cardiac adverse events complicating a previous sclerotherapy treatment; severe acute systemic illness or infection; and critical limb ischaemia. Relative Contraindications to sclerotherapy where the potential benefits of the proposed treatment would outweigh the risk of harm or the risks may be mitigated by other measures include pregnancy, postpartum and breastfeeding; hypercoagulable states with risk of VTE; risk of neurological adverse events; risk of cardiac adverse events and poorly controlled chronic systemic illness. Conditions and circumstances where Warnings and Precautions should be considered before proceeding with sclerotherapy include risk of cutaneous necrosis or cosmetic complications such as pigmentation and telangiectatic matting; intake of medications such as the oral contraceptive and other exogenous oestrogens, disulfiram and minocycline; and psychosocial factors and psychiatric comorbidities that may increase the risk of adverse events or compromise optimal treatment outcomes. Conclusions: Sclerotherapy can achieve safe clinical outcomes provided that (1) patient-related risk factors and in particular all material risks are (1a) adequately identified and the risk benefit ratio is clearly and openly discussed with treatment candidates within a reasonable timeframe prior to the actual procedure; (1b) when an individual is not a suitable candidate for the proposed intervention, conservative treatment options including the option of ' no intervention as a treatment option ' are discussed; (1c) complex cases are referred for treatment in controlled and standardised settings and by practitioners with more expertise in the field; (1d) only suitable individuals with no absolute contraindications or those with relative contraindications where the benefits outweigh the risks are offered intervention; (1e) if proceeding with intervention, appropriate prophylactic measures and other risk-mitigating strategies are adopted and appropriate follow-up is organised; and (2) procedure-related risk factors are minimised by ensuring the treating physicians (2a) have adequate training in general phlebology with additional training in duplex ultrasound, procedural phlebology and in particular sclerotherapy; (2b) maintain their knowledge and competency over time and (2c) review and optimise their treatment strategies and techniques on a regular basis to keep up with the ongoing progress in medical technology and contemporary scientific evidence.